Perancangan Website Publikasi Data Matahari dan Berita Kegiatan BMKG Stasiun Geofisika Kelas III Malang - Husna, Faiza Arifatul (Maliki Interdisciplinary Journal, 2026)
This research aims to design and develop a web-based information system at BMKG Class III Station Malang to publish sunrise and sunset data as well as digitally manage news related to activities. The system is built using the CodeIgniter 4 framework with the Model-View-Controller (MVC) approach, supported by Bootstrap 5 for a responsive user interface. The development process starts from field data collection to system implementation and testing, focusing on improving administrative efficiency and providing easy access to information for the public. As a result, the system successfully replaces the previous manual process that relied on spreadsheets, transforming it into an integrated platform with CRUD features, Excel data upload, and security validation. General users can access information in real time through the user page, while administrators have full control over data management via a dedicated dashboard.